The differentiation of the flora of landscapes in the Pivnichne Prychornomoria (Northern Black Sea Coastal Plain) according to its synantropization (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
This paper presents the results of a comparative analysis of flora with respect to different kinds of landscapes in the Pivnichne Prychornomoria (Northern Black Sea Coastal Plain). The significant role played by synantropization in the differentiation of flora is discussed.
Keywords: Northern Black Sea coastal region, landscape, differentiation of flora, synantropization.